2020
DOI: 10.1029/2019jc015979
|View full text |Cite
|
Sign up to set email alerts
|

Prebomb to Postbomb 14C History From the West Side of Palawan Island: Insights Into Oceanographic Changes in the South China Sea

Abstract: Compared to the natural production of 14C, thermonuclear tests have produced a globally abnormal 14C signal. To examine and reconstruct ocean circulation in the South China Sea (SCS), we generated a prebomb to postbomb 14C time series from a Porites lobata coral from the west side of Palawan Island, Philippines. Results show a diluted early bomb 14C intrusion in late 1955. We use this record to extend our understanding of the surface ocean circulation in and around the SCS by tracing 14C labeled water from nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…This provides an opportunity to examine oceanographic and climate variability using radiocarbon as a seawater tracer over multiple time scales. Many studies have used the 14 C in coral skeletons to track ocean circulation (Druffel 1987;Druffel andGriffin 1995, 1999;Guilderson et al , 2000Guilderson et al , 2009Fallon and Guilderson 2008;Andrews et al 2016a;Hirabayashi et al 2017a;Hirabayashi 2017b;Wu and Fallon 2020). Seawater 14 C has also been shown to be sensitive to large-scale climate phenomena such as the El Niño-Southern Oscillation (ENSO) due to the movement of 14 C labelled water (Druffel andGriffin 1993, 1995;.…”
Section: Introductionmentioning
confidence: 99%
“…This provides an opportunity to examine oceanographic and climate variability using radiocarbon as a seawater tracer over multiple time scales. Many studies have used the 14 C in coral skeletons to track ocean circulation (Druffel 1987;Druffel andGriffin 1995, 1999;Guilderson et al , 2000Guilderson et al , 2009Fallon and Guilderson 2008;Andrews et al 2016a;Hirabayashi et al 2017a;Hirabayashi 2017b;Wu and Fallon 2020). Seawater 14 C has also been shown to be sensitive to large-scale climate phenomena such as the El Niño-Southern Oscillation (ENSO) due to the movement of 14 C labelled water (Druffel andGriffin 1993, 1995;.…”
Section: Introductionmentioning
confidence: 99%
“…The Δ 14 C values of surface seawater DIC are 23.6 ± 2.5‰ higher than the atmospheric Δ 14 C values in the SCS (Figure 2). Due to the atmospheric nuclear bomb test since the 1950s, the atmospheric Δ 14 C values in the Northern Hemisphere (NH) recorded by tree rings (Hua et al., 2013) are higher than corresponding surface seawater Δ 14 C values recorded by coral in the SCS (Bolton et al., 2016; Mitsuguchi et al., 2007; Ramos et al., 2019; Wu & Fallon, 2020) before 2003, resulting in a positive air‐sea Δ 14 C gradient. The gradient gradually switched from positive to negative, due to fossil fuel emissions (Graven, Gruber, et al., 2012).…”
Section: Resultsmentioning
confidence: 99%
“…A previous study showed that the uncertainties of bomb 14 C inventories using pre‐bomb 14 C depth profiles at stations from the same latitudinal belt were less than ±10% (Bhushan et al., 2000). Thus, the pre‐bomb 14 C profile in the SCS was reconstructed approximately from the pre‐bomb Δ 14 C data in the studies in the western Pacific Ocean (Bien et al., 1965; Östlund & Stuiver, 1980), and the SCS (Bolton et al., 2016; Mitsuguchi et al., 2007; Ramos et al., 2019; Wu & Fallon, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations